Manifestasi ‘Asabiyyah dalam Tradisi Tabot Bengkulu: Tinjauan Teoretis Ibn Khaldun - RAFIKO SAPUTRA; Dian Nur Anna Nur Anna (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2025)
The Tabot tradition in Bengkulu constitutes a significant form of religious cultural heritage that integrates strong social, spiritual, and historical values. This study analyzes the tradition through the analytical framework of Ibn Khaldun’s concept of ‘Asabiyyah to understand how collective solidarity, communal unity, and social cohesion are expressed throughout the stages of the Tabot procession. Employing a qualitative research method based on an extensive literature review, the article examines the relationship between the sociocultural values embedded in the Tabot practices and the principles of ‘Asabiyyah, which emphasize unity, group loyalty, and moral strength as the foundations of a dynamic society. The findings reveal that ‘Asabiyyah within the Tabot tradition is manifested not only through the active collective participation of the community but also through its role as a cohesive force that preserves the continuity of the tradition across generations. As such, Tabot extends beyond its function as a religious ritual and emerges as a concrete expression of social solidarity and cultural identity within the Bengkulu community. This interpretation underscores the relevance of classical sociological theory in explaining the resilience and persistence of local traditions in contemporary contexts.